Peripheral Levels of Renin-Angiotensin System Components Are Associated With Cognitive Performance in Huntington’s Disease - Rocha, Natalia P.; Cleary, Courtney; Colpo, Gabriela D.; Furr Stimming, Erin; Teixeira, Antonio L. (Frontiers in Neuroscience, 2020)
The renin-angiotensin system (RAS) has proven to be involved in the pathophysiology of neurodegenerative diseases, such as Parkinson’s disease (PD) and Alzheimer’s disease (AD), serving as a potential therapeutic target and a disease burden marker. Studies have associated negative clinical outcomes with the activation of the classical RAS arm composed of the angiotensin-converting enzyme (ACE) and angiotensin (Ang) II, while suggested positive outcomes with the activation of the counter-regulatory RAS arm involving ACE2 and Ang-(1-7). Huntington’s disease (HD) shares many pathological and clinical outcomes with AD and PD, but the evidence of direct involvement of RAS components in the pathophysiology of HD is still limited and needs further investigation. Herein, we investigated peripheral levels of the RAS components Ang II, Ang-(1-7), ACE, and ACE2 in controls, premanifest, and manifest HD gene carriers and their relationship with clinical outcomes. Peripheral blood samples were collected via phlebotomy, and plasma concentrations of RAS components were measured by Enzyme-Linked Immunosorbent Assay (ELISA). Clinical evaluation included a questionnaire about socio-demographic characteristics, motor, and cognitive assessments. Results showed (1) no significant group differences in plasma concentrations of RAS components; (2) positive correlations between ACE2 and Verbal Fluency Test (VFT) scores; and (3) negative correlations between Ang II and Mini–Mental State Examination (MMSE) scores. These results corroborate the proposed balance between the classical (ACE/Ang II) and the counter-regulatory [ACE2/Ang-(1-7)] arms of the RAS, with the former associated with negative clinical outcomes and the latter with positive effects.